Peran Kepala Madrasah Aliyah sebagai Supervisor Di Pondok Pesantren Al-Ittifaqiah - Febrianto febri Febrianto; Edy Harapan (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
Supervision is an internal part of the education program, supervision is a cooperative service. Transcendental supervision is a series of activities in the context of supervision of the teaching profession. This research was conducted to reveal: 1) the role of the principal as a supervisor at Madrasah Aliyah 2) the factors supporting and inhibiting the role of the principal as a supervisor at Madrasah Aliyah. This type of research is qualitative research. The approach used is qualitative descriptive. The data collection techniques used were interviews, observation, and documentation. And for data analysis techniques using data reduction, data presentation, verification. And using a variety of sources, theories and methods so that researchers obtain objective data. Meanwhile, the research informants were the principal of the madrasah, the curriculum staff, the student staff, the teachers, and the students. The results of this study are: 1). The role of the Madrasah Principal as a Supervisor at Madrasah Aliyah, namely: conducting class visits, holding meetings or meetings, monitoring educators and teaching staff, improving teacher abilities and helping solve problems faced by teachers, improving teaching programs, providing directions to be right on target and appropriate curriculum, improving facilities and infrastructure, creating good communication, assisting teachers in teaching preparation, assisting teachers in using various sources, media, learning and teaching methods and techniques, assisting teachers in carrying out learning evaluations and analyzing learning outcomes, helping teachers analyze difficulties student learning, 2). Supporting and Inhibiting Factors for the principal as a Supervisor at Madrasah Aliyah.